Peningkatan Kemampuan Mengenal Huruf Melalui Permainan Memancing Huruf Bergambar di Taman Kanak-Kanak Aisyiyah 5 Padang - Suryani, Suryani; Aulia, Prima (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The aim of this research is to increase for knowing letters in a child trought a play of fishing some illustrated letters in TK Aisyiyah 5 Padang, in order to the child can mention a first letters of vocal and consonant, arrange some letters to be a word, read a word, and imatate writing. Type of the research is a class action research by using quantitative method. Based on the data obtained from the result of the research in improving the ability to recognize letters throught a play of fishing some illustrated letters has not reached the criteria of minium exhaustiveness yet, so thet the research is continued to the cycle II. On the cycle II, there is the increasing of the ability in knowing letters well and it has reached the criteria of minimum exhaustveness. It shows the increasion of knowing letters in a child